Forensic DNA phenotyping: Privacy breach, bias reification and the pitfalls of abstract assessments of rights - Coquet, Margaux (International journal of police science & management, 2023)
Although the practical benefits of forensic DNA phenotyping (FDP) in criminal investigations remain unclear, this emerging forensic technology is the subject of increasing interest from various European stakeholders. However, the risks that the technology poses to data privacy, as well as its negative impact on racialized sub-populations are well documented. Yet, we argue that the abstract nature of the current legal framework and judicial review allows predictive technologies with uncertain outcomes, such as FDP, to still be considered socially desirable while normalizing their adverse consequences on human rights and social equity. We also argue that criminal law and criminal sciences are in a synergistic relationship in which the reification of socially constructed categories of deviancy by forensic technologies contributes to the legitimization of the repressive apparatus, which in turn calls for the use of more investigative tools despite their inherent pitfalls or limits. We conclude with the need to be mindful of this phenomenon when analysing the social costs attached to emerging forensic technologies, as well as to request disclosure from public authorities of comprehensive data regarding its concrete benefits.